2004
DOI: 10.1021/jp037725k
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Molecular Structure and Bonding of the Surface of Aqueous Salt Solutions

Abstract: The surfaces of aqueous solutions of NaF, NaCl, NaBr, and NaI have been examined using vibrational sum-frequency spectroscopy. Spectra of these salts in mixtures of HOD/H2O/D2O have been used to provide insight into how simple salts alter the hydrogen bonding structure of water in the surface region. As the anion is changed, the observed interfacial hydrogen bonding also changes, indicating the presence of anions in the interfacial region. The isotopic dilution experiments performed on each solution enable sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

54
502
6
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 293 publications
(564 citation statements)
references
References 45 publications
54
502
6
2
Order By: Relevance
“…24,64,74,99,100,101,102,103,104 We suggest that detailed polarization and experimental configuration analysis of the SFG vibrational spectra be applied to these interfaces.…”
Section: Discussionmentioning
confidence: 99%
“…24,64,74,99,100,101,102,103,104 We suggest that detailed polarization and experimental configuration analysis of the SFG vibrational spectra be applied to these interfaces.…”
Section: Discussionmentioning
confidence: 99%
“…107 Vibrational sum frequency spectroscopy of aqueous salt solutions show changes in the interfacial water by the addition of alkali halide salts, although the interpretation in terms of enhancement of interfacial ion concentrations is not as direct. [108][109][110] In light of the MD simulations, surface reactions of Br À and I À would be expected to be even more important than in the case of Cl À . A significant complication in probing these reactions is that the increased reactivity of bromide and iodide ions in bulk solution in many cases overshadows the interface chemistry.…”
Section: Chemistry At the Interface Of Sea Salt Particlesmentioning
confidence: 99%
“…1 However, a combination of computational [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and experimental studies [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] has shown that ions can reside and even be enhanced at the interface.…”
Section: Introductionmentioning
confidence: 99%